Bodily Freezing As A Response To Acute Psychosocial Stress - Richer, Robert; Abel, Luca; Hauck, Felicitas; Ringgold, Veronika; Schindler-Gmelch, Lena; Eskofier, Björn; Rohleder, Nicolas (Psychoneuroendocrinology, 2024)
Background Bodily freezing is a common phenomenon in animals and humans, which is characterized by a temporary immobilization of the body and a reduction in voluntary movement. Although freezing has been observed as a response to social threat, previous studies did not explore full body freezing in the context of acute psychosocial stress. Linking movement patterns to stress could enable the use of movement as a non-invasive marker for stress analysis, replacing invasive stress assessment methods like saliva and blood samples. Methods N=39 participants (44% women; 24.0 ± 3.5 years) completed the Trier Social Stress Test (TSST) and an adapted friendly-TSST (f-TSST) protocol on two consecutive days in randomized order. During the (f-)TSST, participants were equipped with a sensor-based motion capture system, recording full body movement. From this data, we extracted multiple motion features characterizing freezing. Self-reports and salivary cortisol samples were used to measure changes in affect and the physiological stress response, respectively. Results Movement features revealed a significant freezing response when comparing TSST to f-TSST condition (e.g. head [t=5.4, p<0.001]; chest [t=3.8, p<0.001]; total body [t=6.5, p<0.001]), correlating with a significantly larger increase in maximum cortisol levels. In addition, body movement parameters, characterizing freezing, predicted 60% of the variance of maximum cortisol increase between TSST and f-TSST. Conclusion Our study found a strong association between movement features and acute psychosocial stress. It suggests using body movement information as a valuable extension to the existing stress marker